2009
DOI: 10.1182/blood-2008-11-185132
|View full text |Cite
|
Sign up to set email alerts
|

Improved risk classification for risk-specific therapy based on the molecular study of minimal residual disease (MRD) in adult acute lymphoblastic leukemia (ALL)

Abstract: Clinical risk classification is inaccurate in predicting relapse in adult patients with acute lymphoblastic leukemia, sometimes resulting in patients receiving inappropriate chemotherapy or stem cell transplantation (SCT). We studied minimal residual disease (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
298
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(313 citation statements)
references
References 47 publications
12
298
0
3
Order By: Relevance
“…8,9 Owing to its strong predictive value, MRD is being used as a tool for risk stratification in most ALL treatment protocols for both children and adults. [10][11][12] Different techniques are available for monitoring MRD, based either on PCR or multiparametric flow cytometry (MFC). 13,14 Several studies have demonstrated that PCR assays and flow cytometry give complementary results in detecting residual leukemic cells and are currently employed for identification of residual disease and surveillance of disease remission.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Owing to its strong predictive value, MRD is being used as a tool for risk stratification in most ALL treatment protocols for both children and adults. [10][11][12] Different techniques are available for monitoring MRD, based either on PCR or multiparametric flow cytometry (MFC). 13,14 Several studies have demonstrated that PCR assays and flow cytometry give complementary results in detecting residual leukemic cells and are currently employed for identification of residual disease and surveillance of disease remission.…”
Section: Introductionmentioning
confidence: 99%
“…[74][75][76] There is also some evidence in non-APL AML and ALL that treatment intensification (early HCT and/or earlier/additional induction therapy) for patients who are MRD þ after initial therapy may improve outcomes, at least when compared with contemporary cohorts or those MRD þ patients that did not receive the intensified therapy. [77][78][79] Some evidence also suggests benefit of tyrosine kinase inhibitors in BCR/ABL þ ALL with MRD. 80 As MRD levels decrease or become undetectable with intensified therapy, one could postulate that this benefit might translate into improved post-HCT outcomes.…”
Section: Using Pre-hct Mrd To Tailor Therapy In Acute Leukemiamentioning
confidence: 99%
“…Although most adult patients with ALL enter complete remission (CR), only 30% to 40% of patients survive 5 or more years (1). The major cause of treatment failure is relapse, affecting approximately half of the patients who have achieved CR (2).…”
mentioning
confidence: 99%
“…The major cause of treatment failure is relapse, affecting approximately half of the patients who have achieved CR (2). Survival depends on risk factors such as age, white blood cell (WBC) count, time to CR, disease immunophenotype, cytogenetics, and molecular abnormalities (1), and several studies have shown that detection of minimal residual disease (MRD) in childhood and adult ALL is an independent risk parameter of high clinical relevance (3). Early indicators of disease outcome would be particularly useful for the design of new treatments.…”
mentioning
confidence: 99%